Mali : Report on the Observance of Standards and Codes-Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2002)
This report assesses the Observance of Standards and Codes on Fiscal Transparency Module for Mali. Mali has made progress in recent years in increasing the transparency of government operations. The legislative base underlying the budget is extensive. Some modern developments in budgeting, such as the preparation of program budgets that focus on government objectives, have become institutionalized as part of budget preparation, although the organic budget law has not been modified to include the tendency toward focusing on budget outcomes. The budget document presents a clear description of the fiscal and economic outlook.